2019
DOI: 10.1103/physreve.100.032127
|View full text |Cite
|
Sign up to set email alerts
|

Realizable solutions of the Thouless-Anderson-Palmer equations

Abstract: We show that the only solutions of the TAP equations for the Sherrington-Kirkpatrick model of Ising spin glasses which can be found by iteration are those whose free energy lies on the border between replica symmetric and broken replica symmetric states, when the number of spins N is large. Convergence to this same borderline also happens in quenches from a high temperature initial state to a locally stable state where each spin is parallel to its local field; both are examples of self-organized criticality. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Thus, extending RSB to glassy systems on sparse networks, i.e., random graphs [17] of finite average or fixed degree ("Bethe lattices", BL), constituted another major breakthrough [18]. More recently, the one-dimensional long-range model [19] has gained popularity in numerical studies [20][21][22][23] for the ability to interpolate between SK and the EA (but on a 1d -ring geometry) based on the range of interactions. That model has effective upper and lower dimensions, but all results obtained are numerical.…”
mentioning
confidence: 99%
“…Thus, extending RSB to glassy systems on sparse networks, i.e., random graphs [17] of finite average or fixed degree ("Bethe lattices", BL), constituted another major breakthrough [18]. More recently, the one-dimensional long-range model [19] has gained popularity in numerical studies [20][21][22][23] for the ability to interpolate between SK and the EA (but on a 1d -ring geometry) based on the range of interactions. That model has effective upper and lower dimensions, but all results obtained are numerical.…”
mentioning
confidence: 99%
“…The lowest value of the Gibbs potential g m 0 consistent with c 1 = 0, c 2 0 and Σ 0 is again determined analogue to procedure of subsection 3.2. As before a vanishing complexity and two temperature regions are found with a sticking below a different critical temperature [7], to [12] and to [11], respectively.…”
Section: Postulated Marginalitymentioning
confidence: 58%
“…Early numerical investigations [7,[9][10][11] claim marginal metastable states based on c 1 → 0 in the thermodynamic limit. The recent work of Aspelmeier and Moore [12] have numerically studied the N-dependence of the two lowest eigenvalues of the Hessian. They found that both eigenvalues tend to zero in the thermodynamic limit.…”
Section: Postulated Marginalitymentioning
confidence: 99%
See 2 more Smart Citations